Unclear abdominal pain in central emergency admissions: An algorithm Unklare Bauchschmerzen in der zentralen Notaufnahme: Ein Algorithmus - Berner, L.; Dormann, H. (Medizinische Klinik, 2013)
One of the chief complaints in the emergency department is abdominal pain which is associated with a large spectrum of possible underlying diagnoses. Life-threatening diseases have to be identified urgently to treat them rapidly either conservatively or by surgical intervention. The algorithm presented in this article starts with the triage in the emergency department. After triage the first step in the algorithm is an interdisciplinary communication to start the standardized diagnostic process which includes medical history, clinical examination, laboratory analyses, ultrasound and electrocardiogram. Further diagnostic escalation should be done in unspecific and urgent cases of abdominal pain after consulting a specialist. In approximately 30 % of patients with abdominal pain on admittance to an emergency department the cause remains unclear after undergoing the diagnostic process. In these cases it can be useful for risk stratification to transfer the patient to a ward related to the emergency department for observation und further diagnostics. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Chief complaint; Diagnostic standards; Emergency medicine; Quality assurance; Risk stratification